Comparative Legal and Economic Analysis of Franchising - Namsrai, Battulga (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
Franchising is a business model that has been converting dozens of intangible assets into tangible in the history of mankind. Thus, nowadays it by itself covers a wide range of institutional aspects of law and economics. Besides, a franchise runs according to Nash’s Equilibrium theory. A player can achieve the desired outcome by not deviating from their initial strategy. For this purpose, the franchisor provides an amount of assistance to the franchisee in starting and managing the business activities. De facto, principles of equality are slightly different for franchise contracts. This is because the results of the contract cannot be achieved without the strict supervision and advice of the license holder. Therefore, this short comparative research has considered legal and business issues relating to franchise, including the main contract law requirements, the disclosure obligation, patent protection, vertical restraints, and the general economic outcome of franchising in some countries.